2018
DOI: 10.3390/geriatrics3030043
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning for Older People with Cancer and Its Implications in Asia: Highlighting the Mental Capacity and Relational Autonomy

Abstract: With dramatically increasing proportions of older people, global ageing has remarkably influenced healthcare services and policy making worldwide. Older people represent the majority of patients with cancer, leading to the increasing demand of healthcare due to more comorbidities and inherent frailty. The preference of older people with cancer are often ignored, and they are considered incapable of making choices for themselves, particularly medical decisions. This might impede the provision of their preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
(71 reference statements)
0
30
0
Order By: Relevance
“…The findings of this study provide useful insight for professionals within and beyond the UK, as healthcare systems around the world increasingly recognise the importance of ACP in end-of-life care [33–35] and the need to implement electronic patient records to facilitate the delivery of appropriate care [19, 20]. This study has identified a need, and strong desire, for improved access to accurate and in-date ACP documentation for paramedics attending patients at end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study provide useful insight for professionals within and beyond the UK, as healthcare systems around the world increasingly recognise the importance of ACP in end-of-life care [33–35] and the need to implement electronic patient records to facilitate the delivery of appropriate care [19, 20]. This study has identified a need, and strong desire, for improved access to accurate and in-date ACP documentation for paramedics attending patients at end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…This practice may be influenced by the Japanese legal system and culture, which prefers decision‐making by groups rather than individuals. In East Asia, many patients favour “joint decisions” about EOL care, while accepting the necessities of advance directives (Ivo et al, ); moreover, Lin, Cheng, and Chen () described relational autonomy as a practical approach for older adults in Asia. Thus, cultural consideration is an important aspect of EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…In the Asia-Pacific region, the trend of involving patients in medical decision-making is receiving increasing attention. 1215 This has been driven by political initiatives and legislation (or guidance) that recognise an individual’s autonomy 16 (e.g. Patient Right to Autonomy Act in 2016 in Taiwan 17 and Mental Capacity Act in Singapore 14 ).…”
Section: Introductionmentioning
confidence: 99%